2012
DOI: 10.1177/1367006912439940
|View full text |Cite
|
Sign up to set email alerts
|

Proactive interference between languages: Do task demands matter?

Abstract: A recent discovery of research on bilingualism is that a bilingual’s two languages are both active during online speech production and comprehension. Speakers may manage the interference that arises from possessing two simultaneously active languages by inhibiting the language that is task inappropriate or enhancing the activation of the language they intend to use. These accounts were assessed by examining the consequences of earlier use of a language on the current use of another language and by determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Interference is effect that is given by process of the other language learning because of learner"s language background. In addition, the interference arises from possessing two simultaneously active languages by inhibiting the language that is tasking inappropriate or enhancing the activation of the language they intend to use [8]. As nearly all new skills are learned on the basis of existing skill, skill research has traditionally shown a keen interest in the phenomenon of transfer.…”
Section: B the Concept Of Interferencementioning
confidence: 99%
“…Interference is effect that is given by process of the other language learning because of learner"s language background. In addition, the interference arises from possessing two simultaneously active languages by inhibiting the language that is tasking inappropriate or enhancing the activation of the language they intend to use [8]. As nearly all new skills are learned on the basis of existing skill, skill research has traditionally shown a keen interest in the phenomenon of transfer.…”
Section: B the Concept Of Interferencementioning
confidence: 99%